A SEMANTIC ANALYSIS OF WORDS “KHALAQA, JA’ALA, BADA’A, SHANA’A, FATHARA” IN REVEALING THE CONCEPT OF HUMAN CREATION - Yayan Nurbayan (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2019)
This qualitative research argues that the concept of human creation in the holy Quran can be revealed by analyzing the words khalaqa, ja’ala, bada’a, shana’a, and fathara. In doing the analysis, the meaning of words is characterized based on lexical, grammatical, and contextual aspects. This research found that there are only two words used in verses concerning human creation, namely ‘خلق، جعل’ / ‘ja’ala, khalaqa’. The word khalaqa is an intransitive word (fi’il muta’addy) consisting of a single object (maf’ul). Furthermore, the word ‘جعل’ is a transitive verb consisting of two objects (muta’addi bi maf’ulaini). In the context of human creation, the word is used to describe the function of human beings. The word جعل functions as an element to describe the role of an object in the respective verses.